Desenvolvimento de procedimentos automáticos para a determinação de 3-hidroxibutirato, glicose e colesterol em soro de sangue animal empregando multicomutação em fluxo - Pires, Cherrine Kelce (2003)
In the present work, in flow injection systems were developed for the determination of important metabolic parameters, such as 3-hydroxybutyrate, glucose and cholesterol in animal blood serum. The analysis modules were developed based on the multicommutation concept, whose main characteristics favor the processing of many samples. For this, three-way solenoid valves were used, as discreet commutation devices, for the intermittent addition of samples and reagents, controlled by a microcomputer equipped with a commercial electronic interface (PCL-711S). The control and data acquisition programs were written in Quick BASIC 4.5. The proposed methods are based on enzymatic reactions. For these, the enzymes were immobilized in glass beads and packed in mini-columns of acrylic (15 x 5 mm i.d.). The determination of 3-hydroxybutyrate was based on the reduction of nicotinamide adenine dinucleotide (NAD+), forming NADH, which was monitored at 340 nm. The analytical curve of the proposed system presented a linear dependence on concentration for concentrations between 25 and 150 mg L-1, an analytical frequency of 60 determinations per hour, relative standard deviation of 1.4% (n=17), estimated for a sample containing 75 mg L-1 of 3-hydroxybutyrate, and a detection limit of 2 mg L-1. Other observed favorable aspects were low reagent consumption of NAD+ (0.9 mg) and 3-hydroxybutyrate dehydrogenase (8 µg), and 200 µL of sample per determination. Another analysis module was developed for glucose determination using chemiluminescence detection. The glucose was oxidized by glucose oxidase to gluconic acid and hydrogen peroxide. The hydrogen peroxide formed reacted with the luminol, in the presence of the catalyst hexacyanoferrate (III), producing a blue luminescence at a wavelength around 420 nm. The analytical curve of the proposed system was linear for concentrations between 50 and 600 mg L-1, showed a relative standard deviation <3.0% (n=20) for a sample containing 300 mg L-1 of glucose, a detection limit of 14.0 mg L-1, and an analytical frequency of 60 determinations per hour. The sample, hexacyanoferrate (III) and luminol consumption was 46 µL, 10.0 mg and 0.2 mg per determination, respectively. To conclude this work, the determination of cholesterol was proposed. The esters of cholesterol were hydrolyzed by cholesterol esterase to free cholesterol and fatty acid. The free cholesterol was oxidized by cholesterol oxidase to cholestenone and hydrogen peroxide. The hydrogen peroxide reacted with luminol and hexacyanoferrate (III), being detected by chemiluminescence. The proposed system presented an analytic frequency of 40 determinations per hour, relative standard deviation of 2.3% (n=20) for a sample containing 75 mg L-1 of cholesterol, a linear dependence in the concentration range of 25 and 125 mg L-1, and an estimated detection limit of 3.7 mg L-1. The reagent consumption was 0.22 mg of luminol and 2.75 mg of hexacyanoferrate (III) per determination. Once the best analysis conditions were found, a set of samples was analyzed using the three proposed systems. Applying the t test among the results obtained with the proposed systems and those obtained with the manual procedures of analysis (kit), no significant difference was observed at the 95% confidence level.